Roles of preoperative anxiety and depression in the outcomes of microvascular decompression in hemifacial spasm for adolescent patients. Issue 32 (13th August 2021) - Wu, Fan; Wei, Pingcun; Wang, Gang; Wu, Changsong; Hu, Yunlong; Hu, Jinwang
Abstract : Abstract: Hemifacial spasm (HFS) has been recognized as the frequently occurring disease of cranial nerve. At the same time, several articles indicate that, dystonia results in certain psychological disorders. Consequently, this study aimed to examine the association of preoperative depression and anxiety with HFS severity; meanwhile, the role in microvascular decompression (MVD) outcomes after surgery among adolescent patients was also examined. All cases had been classified as two groups based on MVD outcomes among HFS cases; in addition, the preoperative Hamilton anxiety rating scale (HARS) and the Hamilton depression rating scale (HDRS) scores were compared between patients not and still suffering from spasm. Moreover, the multiple logistic regression model was employed in assessing the relationship between preoperative HARS as well as HDRS scores and outcomes of adolescent cases undergoing MVD. The preoperative HARS and HDRS scores showed positive correlation with Cohen spasm grades in HFS patients. Meanwhile, compared with spasm-free group, patients of persistent spams group had apparently higher preoperative HARS and HDRS scores. Our results suggest that, preoperative anxiety and depression status show close association with HFS severity, and they could also impact the MVD outcomes for adolescent cases.